2014
DOI: 10.1109/tmm.2014.2328324
|View full text |Cite
|
Sign up to set email alerts
|

Joint Sampling Rate and Bit-Depth Optimization in Compressive Video Sampling

Abstract: Compressed sensing is a novel technology that exploits sparsity of a signal to perform sampling below the Nyquist rate, and thus has great potential in low-complexity video sampling and compression applications, due to the significant reduction of the sampling rate ( ) and computational complexity. However, most current work about compressive video sampling (CVS) has focused on real-valued measurements without being quantized, and thus is not applicable to engineering practices. Moreover, in many circumstances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Meanwhile, generating a different measurement matrix for every signal could be energy-consuming. Additionally, for engineering practice, using the same measurement matrix for multiple signals or signal segments flavors the subsequent source coding stage of multimedia data sensing, as discussed in [17], [18]. Based on these observations, it is concluded that investigating the behavior of CS-based cipher under the multi-time-sampling (MTS) scenario is both important from the cryptographic and engineering point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, generating a different measurement matrix for every signal could be energy-consuming. Additionally, for engineering practice, using the same measurement matrix for multiple signals or signal segments flavors the subsequent source coding stage of multimedia data sensing, as discussed in [17], [18]. Based on these observations, it is concluded that investigating the behavior of CS-based cipher under the multi-time-sampling (MTS) scenario is both important from the cryptographic and engineering point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the CS quantization, the number of measurements (M ) and the number of bits per measurement (bit-depth (B)) represent the main tradeoffs in the rate-distortion (RD) performance [3]. An empirical distortion model for compressed video sensing (CVS) is proposed in [4], along with a rateallocation module for both the sampling rate (SR) and the quantization bit-depth for each block in video frames. However, in [4], the distortion model parameters are sequence dependent.…”
Section: Introductionmentioning
confidence: 99%
“…An empirical distortion model for compressed video sensing (CVS) is proposed in [4], along with a rateallocation module for both the sampling rate (SR) and the quantization bit-depth for each block in video frames. However, in [4], the distortion model parameters are sequence dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also obtains the information of local complex structure in natural images, and fully exploits the redundancy between frames by combining the block matching technique commonly used in video. Because of these advantages mentioned above, the application of BCS in DCVS has been researched considerably (Do et al 2009;Prades-Nebot et al 2009;Fowler et al 2012;Liu et al 2013Liu et al , 2014. Among them, the BCS-based multi-hypothesis (MH-BCS) scheme has gained wide spread attention due to its high recovery quality.…”
Section: Introductionmentioning
confidence: 99%